Functional Mitral and Tricuspid Regurgitation : Pathophysiology, Assessment and Treatment - Chan, Kok Meng John (Springer International Publishing : Imprint: Springer, 2017)
This book covers in detail all aspects of functional mitral and tricuspid regurgitation, from its pathophysiology and natural history, to its assessment, medical and surgical treatment, and long term results. Functional Mitral and Tricuspid Regurgitation encompasses information and knowledge from a diverse background including cardiology, cardiac surgery and basic science. This is necessary for a full understanding of the subject in order to optimally manage patients with this condition.
Keywords: Medicine.; Cardiac imaging.; Cardiology.; Cardiac surgery.; elektronické knihy; electronic books